The Human Tragicomedy: the Reception of Apuleius' Golden Ass in the Twentieth and Twenty-First Century - Mickiewicz, Adam,; Stróżyński, Mateusz, (Classical Studies E-Books Online, Collection 2024., 2024)
Does the story of Lucius, a curious and lustful young man who is magically transformed into an ass, have anything to teach us today? Does it have a serious, philosophical and religious meaning, or is it just a form of literary play, full of adve